Understanding cyclist traffic behaviour: Contrasting cycle path designs in Santiago de Chile. (November 2016) - Waintrub, Natan; Peña, Carolina; Niehaus, Markus; Vega, Rodrigo; Galilea, Patricia
Abstract: Cities around the world have experienced an increase in the number of cyclists, which has resulted in a demand for more cyclist infrastructure. In Santiago de Chile, each local government is in charge of providing bicycle infrastructure according to its own technical and financial restrictions. Thus, infrastructure dedicated to bicycles has increased, but its quality and design standards differ across the city. This creates an ideal test-bed for understanding how cyclists' behaviour changes under different cycle path designs. The objectives of this research are (i) to explore the conditions of Santiago's cycle path intersections in terms of speed and urban characteristics and (ii) to understand cyclists' behaviour under different cycle path conditions. Some characteristics of cycle path intersections measured were cycle path's length, slope, lateral clearance, physical segregation, bi-directionality, obstacles, and discontinuities. Also, data taken characterise users by gender and use of helmet. Linear regression models were calibrated to explain cyclists' speed using intersection characteristics. According to our model, relevant characteristics were location of cycle path, physical segregation, percentage of female users, slope, and existence of vertical discontinuities. We hope that our results will serve as a guide for public authorities on the design of cycle paths.